2022
DOI: 10.1038/s41536-021-00203-6
|View full text |Cite
|
Sign up to set email alerts
|

The clinical potential of articular cartilage-derived progenitor cells: a systematic review

Abstract: Over the past two decades, evidence has emerged for the existence of a distinct population of endogenous progenitor cells in adult articular cartilage, predominantly referred to as articular cartilage-derived progenitor cells (ACPCs). This progenitor population can be isolated from articular cartilage of a broad range of species, including human, equine, and bovine cartilage. In vitro, ACPCs possess mesenchymal stromal cell (MSC)-like characteristics, such as colony forming potential, extensive proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 114 publications
(302 reference statements)
0
20
0
Order By: Relevance
“…Termed articular cartilage-derived progenitor cells (ACPCs), these cells most likely reside in the superficial zone in healthy cartilage and will migrate toward the sites of cartilage injury ( Grogan et al, 2009 ; Williams et al, 2010 ). These cells show similar markers to those of MSCs (CD90, CD105, CD73, and CD166) ( Rikkers et al, 2022 ), possibly distinguished phenotypically by an increased expression of CD44 and enhanced expression of fibronectin and integrin-α5β1 ( Dowthwaite et al, 2004 ; Levato et al, 2017 ), suggesting a unique progenitor cell population. Correspondingly, OA joint-derived ACPCs were shown to form more colonies in vitro compared to those from healthy human cartilage, suggesting greater proliferation capacity with increasing OA severity ( Wang et al, 2020 ; Rikkers et al, 2022 ).…”
Section: Recruiting and Stimulating Endogenous Stem Cells To Treat Os...mentioning
confidence: 97%
See 3 more Smart Citations
“…Termed articular cartilage-derived progenitor cells (ACPCs), these cells most likely reside in the superficial zone in healthy cartilage and will migrate toward the sites of cartilage injury ( Grogan et al, 2009 ; Williams et al, 2010 ). These cells show similar markers to those of MSCs (CD90, CD105, CD73, and CD166) ( Rikkers et al, 2022 ), possibly distinguished phenotypically by an increased expression of CD44 and enhanced expression of fibronectin and integrin-α5β1 ( Dowthwaite et al, 2004 ; Levato et al, 2017 ), suggesting a unique progenitor cell population. Correspondingly, OA joint-derived ACPCs were shown to form more colonies in vitro compared to those from healthy human cartilage, suggesting greater proliferation capacity with increasing OA severity ( Wang et al, 2020 ; Rikkers et al, 2022 ).…”
Section: Recruiting and Stimulating Endogenous Stem Cells To Treat Os...mentioning
confidence: 97%
“…These cells show similar markers to those of MSCs (CD90, CD105, CD73, and CD166) ( Rikkers et al, 2022 ), possibly distinguished phenotypically by an increased expression of CD44 and enhanced expression of fibronectin and integrin-α5β1 ( Dowthwaite et al, 2004 ; Levato et al, 2017 ), suggesting a unique progenitor cell population. Correspondingly, OA joint-derived ACPCs were shown to form more colonies in vitro compared to those from healthy human cartilage, suggesting greater proliferation capacity with increasing OA severity ( Wang et al, 2020 ; Rikkers et al, 2022 ). An increase in progenitor markers, such as CD271 ( Wang et al, 2020 ), CD105 ( Zhang et al, 2016 ), and VCAM ( Grogan et al, 2009 ) at sites of trauma or in OA cartilage were also observed.…”
Section: Recruiting and Stimulating Endogenous Stem Cells To Treat Os...mentioning
confidence: 97%
See 2 more Smart Citations
“…CSPCs are characterized by the traditional MSC markers individually or in combination, including CD105, CD73, CD54, CD106, CD166, CD9, CD90, CD146, CD44e, and CD271 ( Figure 1 B) [ 24 , 33 , 36 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Additionally, some studies have distinguished CSPCs in articular cartilage more specifically by using markers such as laminin, integrin-α5β1, Jagged, Notch-1, Notch-2, Delta, and STRO 1 [ 42 , 45 , 48 , 57 , 58 , 59 ]. However, none of the above studies identified a CSPC-specific marker to directly identify and distinguish them from MSCs and chondrocytes either in vitro or in vivo.…”
Section: Markers Of Cspcsmentioning
confidence: 99%